Labour Arbitration of Co-Worker Sexual Harassment Cases in Canada - Hart, Susan M. (Canadian Journal of Administrative Sciences / Revue Canadienne des Sciences de l'Administration, 2012)
Women have the right to a workplace free from sexual harassment under Canadian provincial and federal human rights legislation. Canadian labour laws incorporate the right to a grievance procedure including binding arbitration where arbitrators must interpret and apply human rights legislation. This paper analyzes co-worker sexual harassment cases in order to assess how well arbitrations protect the right of unionized women to a harassment free workplace. Results indicate that women complainants were often subjected to aggressive gendered cross-examinations and the application of gendered jurisprudence that largely ignored the impact of gendered power relations in the workplace. The conclusion is that women's experiences in arbitrations are likely a deterrent to filing formal complaints, effectively undermining rather than protecting their rights.
Keywords: arbitrage des conflits du travail; co-worker sexual harassment; droits de la personne; droits des femmes; harcèlement sexuel; harcèlement sexuel de la part des collègues; human rights; labour arbitrations; sexual harassment; women's rights